CITRA DAN PERSEPSI HARGA DALAM MEMPENGARUHI KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (STUDI PADA PELANGGAN BUSSINES CENTRE SMK NEGERI 2 SEMARANG) - Handayani, Wilujeng; Soliha, Euis (Proceeding SENDI_U, 2015)
This study aimed to examine the effect of image and price perception on customer satisfaction, the effect of image, priceperception and of customer satisfaction on customer loyalty. This study do to customer of Business Centre SMK Negeri 2Semarang. By using purposive sampling, obtained to 100 respondents, who make a purchase at least two (2) times a year, asa specific target. The results of this study show that image and price perception, are positive and significant take effect oncustomer satisfaction. Image are not positive and significant take effect on customer loyalty and price perception are positiveand significant take effect on customer loyalty. And than customer satisfaction positive and significant take effect oncustomer loyalty Business Centre SMK Negeri 2 Semarang.Keywords: Image, Price Perception, Customer Satisfaction and Customer Loyalty.